جماليّات اللُّغة والشّعر عند مارتن هيدجر - محمد, أحمد; سليمان, مازن (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تعدَّت اهتمامات الفيلسوف الألماني "هيدجر" الحقل الفلسفي الصِّرف, خاصةً في مراحل تفكيره المتقدمة, التي امتازت بمقارباته الجماليّة-الأنطولوجية للّغة والشِّعر؛ الأمر الذي ترك آثاراً عميقة على النظرية النقدية الحديثة حتَى وقتنا الحاضر. لقد أراد هيدجر أن يتجاوز الفلسفة التقليدية التي نسيت اختلاف الوُجود عن الموجود نتيجةً لانشغالها بالموجود الماثل أمامها. ليمثل جهده فتحاً كبيراً, بنى عليه فهمه للغة والشعر ابتداءً من إعادة النظر في مفهوم الحقيقة, والتي أصبحت تعني في تفكيره الكشف (أليثيا) وليس المطابقة. نعرض في هذا البحث بعضاً من أهمّ إضافات هيدجر النوعية التي أغنت النقد والجماليات؛ ولاسيما فيما يخص تعريفه للغة بِوصفها بيتاً للوجود, وتأويله للنص الشعري بِوصفه كشفاً أنطولوجياً يفتح عالَماً على طريقته. The German Philosopher Heidegger's concerns were deeper than the abstract field of philosophy. The advanced stages of his thinking were characterized by his aesthetic, ontological approaches to language and poetry; this has had its profound impact on the new theory of criticism. Heidegger attempted to surpass classical philosophy which overlooked the difference between existence and nonexistence owing to its being preoccupies with present-day existence. Thus, his effort proved to be a great success reflected in his understanding of language and poetry by reviewing the concept of truth, whose meaning became more explanatory (Alethia) than obsequious. We present in this research some of Heidegger's contributions which enriched criticism and aesthetics, especially his definition of the language as an embodiment of being and his interpretation of the poetic text as an ontological breakthrough exploring a world of its own.